Aggregating 'Hass' avocado fruit before packing. Issue 2 (3rd July 2022) - Burdon, Jeremy; Billing, David; Wohlers, Mark; Gray, Helen
ABSTRACT: 'Hass' avocado fruit are usually packed the day after harvest and then immediately cooled and held no more than a few days before export. This procedure is considered to maximise the storage life and quality of the fruit. However, for packhouse logistics, there are times when it may be advantageous to aggregate fruit over a period of days before packing. It is hypothesised that the time at which fruit are cooled may be more significant to fruit quality than the time of packing. The impact of holding fruit at 7°C for up to 6 days before packing and cooling to storage temperature (5°C) has been investigated. In comparison with fruit held overnight at ambient conditions before packing and cooling, the holding of fruit at 7°C for up to 4 days before packing did not diminish the quality of the fruit markedly, either immediately out of storage (4 weeks after harvest) or after ripening at 20°C. Extending the holding period to 6 days may increase slightly the risk of fuzzy patches, stem end rots and body rots. However, there was as much variability in the incidence of disorders among orchards as there were differences among treatments.